On the rebound: Symptoms of acute hyperphagia in an international level male taekwondo athlete following chronic body mass loss - Langan-Evans, C.; Germaine, M.; Artukovic, M.; Shepherd, S. O.; Close, G. L.; Morton, J. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Rebound hyperphagia is classified as the overcompensation of both body (BM) and fat (FM) masses following periods of chronic energy deficit. This phenomenon was first studied in the early 1900`s and characterised during the seminal Minnesota Starvation Experiment by Ancel Keys and colleagues. Combat sport athletes represent a key population who are particularly susceptible to this condition, given they chronically lose BM for sequential competitions across their careers. The aim of this study was to examine potential acute rebound hyperphagia in a male international level Taekwondo athlete, following a chronic period of BM loss. Post competition, across a seven-day period, the athlete had their daily energy intake (EI) tracked utilising the `Snap-n-Send` method. Body composition was assessed via Dual X-ray Absorptiometry and metabolic profile/energy deficiency were examined via resting metabolic rate (RMR). Venous blood sampling for measures of endocrine/lipid profiles in tandem with cardiac screening and psychological assessment via semi structured interviews were all collected at regular intervals. Following a pre competitive BM loss of 9.8 kg (14%), there was a rebound of 8.3 kg (13%), accompanied by a 1.5 kg (15%) increase in FM. Pre competition average EI was set at 11,900 kcal·wk-1, which was substantially increased to 33,000 kcal·wk-1 in the ad libitum post competitive period. This resulted in a marked increase in RMR from baseline by over 390 kcal·day-1 (23%) and 650 kcal·day-1 (45%) prior to competition. Despite rescuing a number of HPG axis hormones to baseline reference levels, this also resulted in unfavourable increases in triglyceride and total cholesterol/HDL/LDL lipid profiles. Additionally, the athlete exhibited marked hyperinsulinemia, with an increase of over 116 pmol·L-1 (446%) compared to average pre-competitive values. This study represents the first time a psycho-physiological assessment of rebound hyperphagia has been conducted within combat sports. The post competitive period represents a critical time in an athletes` nutritional recovery, which can result in pronounced negative health effects if neglected. Future research should examine this condition for longer time phases and across repeated periods to better understand how to address this issue.